Engaging Students in Retrieval Practice Over Academic Breaks - van de Sande, Carla (International Journal of Learning and Development, 2024)
Students lose valuable ground over breaks from school, and this issue is even more problematic given the detrimental effects of the COVID-19 pandemic on student progress and learning. The Keep in School Shape (KiSS) Program represents a way of engaging students in reviewing previously learned material that they need to maintain over academic breaks. The KiSS program repurposes existing online survey software to nudge students to engage in daily retrieval practice opportunities via text message or email, together with supporting resources, including hints, solutions, and empowering feedback messages. This paper describes the design of the KiSS Program and presents select results for a run of the KiSS Program during the 2022 winter break involving introductory level Calculus students at a large university. Findings indicate that such a program can get students to voluntarily rehearse previously learned material over breaks from school, and that students use the program in ways that are consistent with a growth mindset.